The Precedence of the Absolute Object on its Governor: A Descriptive and Semantic Study in the Holy Quran - Al- Hawawsha, Sayel (Dirasat: Human and Social Sciences, 2021)
Most Arabic grammarians traditionally shunned the issue of whether the Absolute Object (al-mafʿūl al-muṭlaq) could precede it governor. This was an arduous mission that required rooting through syntax books and interpretations of the Holy Quran, in order to identify any genuine or artificial examples, that support one opinion over another in this regard, or to refute it, while providing an overview of the opinions of Arabic grammarians and exegetes of the Holy Quran, which were more than ten.As the adjective that replaces the noun (al-masdar) was the only case where the absolute object (al-mafʿūl al-muṭlaq) preceded its governor, this paper aims to determine the conditions or factors that allow or forbid dropping the noun (al-masdar). Additionally, this paper aims at determining the detonations related to the absolute object when it precedes its governor, by reference to the Quranic verses that used this structure, and comparing them to other normal examples that uses the common arrangement.A key result of this paper is that it asserts the admissibility of omitting the adjective-bound masdar if its grammatical status is marked after being dropped. If it is an object “mafʿūl bihi”, or a circumstantial adverb “hal”, or an adverb, it is permissible to keep the masdar or drop it, otherwise it could not be omitted.